30 Points if you can answer my question

Justify each step in solving the equation by writing a reason for each statement.

Given: 6x = 3 ( x + 4 )

Prove: x = 4


https://imgur.com/PD2e0TO

Respuesta :

Answer:


Step-by-step explanation:

6x=3(x+4) distribute the 3 to the x and the 4 in the parenthesis to get 6x=3x+12 then subtract 3x on both sides to get 3x=12 last step is to divide by 3 on both sides so x is by itself and all you have left is 12/3 which would leave you with x=4



ACCESS MORE